Towards Modeling the Structure of Product Dependencies in Supply Networks to Identify Bottlenecks Among Suppliers - Henselmann, Daniel; Harth, Andreas (Proceedings of the Third International Workshop on Linked Data-driven Resilience Research (D2R2’24) co-located with European Semantic Web Conference 2024 (ESWC 2024), 2024)
This paper introduces an ontology-based approach to model supply networks aimed at identifying bottlenecks among suppliers. Considering concepts from existing ontologies, we develop a concise ontology to represent the structure of supply networks, focusing on products and their derivational dependencies. We compare our ontology to PRONTO, a heavyweight ontology with a similar scope, demonstrating its reduced complexity while retaining sufficient modeling capabilities. Reduced expressiveness in some product cases due to the abstraction of product variants is a limitation. Further work is needed on network metrics and measures to identify bottlenecks.<br
Keywords: supply network; bottlenecks; graph model; ontology